Enhanced oral absorption of insulin: hydrophobic ion pairing and a self-microemulsifying drug delivery system using a D-optimal mixture design. (31st December 2022) - Goo, Yoon Tae; Lee, Sangkil; Choi, Ji Yeh; Kim, Min Song; Sin, Gi Hyeong; Hong, Sun Ho; Kim, Chang Hyun; Song, Seh Hyon; Choi, Young Wook
Abstract: The lipophilicity of a peptide drug can be considerably increased by hydrophobic ion pairing with amphiphilic counterions for successful incorporation into lipid-based formulations. Herein, to enhance the oral absorption of insulin (INS), a self-microemulsifying drug delivery system (SMEDDS) formulation was developed. Prior to optimization, INS was complexed with sodium n -octadecyl sulfate (SOS) to increase the loading into the SMEDDS. The INS–SOS complex was characterized via scanning electron microscopy, Fourier transform infrared spectroscopy, differential scanning calorimetry, and its dissociation behavior. The SMEDDS was optimized using a D-optimal mixture design with three independent variables including Capmul MCM ( X 1, 9.31%), Labrasol ( X 2, 49.77%), and Tetraglycol ( X 3, 40.92%) and three response variables including droplet size ( Y 1, 115.2 nm), INS stability ( Y 2, 46.75%), and INS leakage ( Y 3, 17.67%). The desirability function was 0.766, indicating excellent agreement between the predicted and experimental values. The stability of INS-SOS against gastrointestinal enzymes was noticeably improved in the SMEDDS, and the majority of INS remained in oil droplets during release. Following oral administration in diabetic rats, the optimized SMEDDS resulted in pharmacological availabilities of 3.23% (50 IU/kg) and 2.13% (100 IU/kg). Thus, the optimized SMEDDS is a good candidate for the practical development of oral delivery of peptide drugs such as INS.